Averaging of aperiodic problems of control over fracture surfaces - Zverkova, T. S.; Plotnikov, V. A.; Slobodyanyuk, O. E. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
An averaging method is justified for standard aperiodic systems with parameters and discontinuous right-hand sides under the condition of aperiodicity and applied to the problems of control over fracture surfaces.